Pengamanan Internet of Things Berbasis NodeMCU Menggunakan Algoritma AES Pada Arsitektur Web Service REST - Ariyan Zubaidi; Rhomy Idris Sardi; Andy Hidayat Jatmika (Universitas Hamzanwadi, 2021)
Data confidentiality and resource's limitation issues are challenges for the Internet of Things. To implement good security on IoT systems, cryptography can do it, but it needs an effective encryption algorithm that does not require a lot of resources. The purpose of this study is to secure an IoT system by implementing an algorithm that is successful in maintaining the confidentiality of data transmitted. This research uses an experimental approach, by creating an IoT system for agriculture and adding an encryption algorithm. The IoT system uses NodeMCU as a microcontroller. NodeMCU is a microcontroller with small resources so it needs an efficient algorithm to be implemented in it. One algorithm that has good performance in a desktop computing environment is the Advance Encryption Standard (AES) algorithm. The algorithm is tested in an IoT computing environment with a data exchange architecture using an REST (Representational State Transfer) web service, resulting in an IoT system for agriculture with cryptographic implementations in it. In the tests carried out, the encryption process of 128 and 256 bits of plain text took 266.31 and 274.31 microseconds, while the memory used was 16% and 17% of the total memory, respectively. This shows the encryption time is fast, and the memory usage is relatively small.